MANAJEMEN PEMBELAJARAN PROJECT BASED LEARNING KEGIATAN PELATIHAN TIE DYE SHIBORI PENGABDIAN MASYARAKAT SMK MAHDATUL ILMI MUARA GEMBONG BEKASI - Suliyanthini, Dewi; Noerharyono, M (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract The purpose of implementing project based learning learning was the tie dye shibori training activity to motivate the community, teachers and students of Mahdatul Ilmi Vocational School to make T-shirt products and tie dye shibori fabrics, as souvenir project souvenirs at Pakis Muara Gembong Bekasi beach, which has implications for improving the community's economy towards an independent village. Methods of training with project methods, tutorials, experiments, evaluation of pretest-posttest activities and satisfaction of activity results. The results of the activity, obtained an average pretest score of 65 or 0.3 and a very high posttest score of 100. Measurement value of satisfaction results 98% of participants were very satisfied with this training. The results of interviews on the sustainability of the activities, the participants were very enthusiastic about making products again as land to add to the economy. Abstrak Tujuan dari implementasi pembelajaran project based learning kegiatan pelatihan tie dye shibori ini untuk memotivasi masyarakat, guru-guru dan siswa SMK Mahdatul Ilmi membuat produk T-shirt dan kain tie dye shibori, sebagai project souvenir oleh-oleh di pantai Pakis Muara Gembong Bekasi, yang berimplikasi pada peningkatan perekonomian masyarakat menuju desa mandiri. Metode pelatihan dengan metode proyek, tutorial, ekperimen, evaluasi kegiatan pretest-postest dan kepuasan hasil kegiatan. Hasil kegiatan, diperoleh nilai pretest rata-rata 65 atau 0,3 dan nilai posttest 100 sangat tinggi. Nilai pengukuran hasil kepuasan 98% peserta sangat puas dengan pelatihan ini. Hasil wawancara keberlanjutan kegiatan, peserta sangat antusias membuat produk kembali sebagai lahan menambah perekonomian.